Hábitos alimenticios de los estudiantes del programa de enfermería de la Universidad Antonio Nariño, sede Buganviles (Neiva, Huila) (2022)
Nutrition in humans has been defined as the processes by which cells, tissues, organs, systems, and the body obtain and use nutrients from food to maintain the integrity of the structures and functions of the organism (1). Nutrition plays an essential role since it has been pointed out that the combination and adequate amounts of nutrients in food are those that determine health (1), which is based on the food that consists of the mechanism in which the body takes from the outside food substances (2). For this reason, the relationship between the amount of consumption, preparation and quality of food are part of the practices food